Arsenic-bearing phases in South Andean volcanic ashes: Implications for As mobility in aquatic environments - Bia, Gonzalo Luis (2015)
Three samples of volcanic ashes collected after eruptions of the volcanos Hudson in 1991, Chaitén in 2008 and Puyehue in 2011 were analyzed in order to define the solid speciation of arsenic and the dynamics of its release to the aqueous phase. The bulk chemical and mineralogical characterization of the samples was performed by ICP/OES, DRX, and SEM/EDS analyses. The chemical composition of the near surface region (first 2-10. nm), along with the As and Fe solid speciation was performed by XPS. Batch experiments were conducted to evaluate the kinetics of the arsenic release under variable pH conditions. The integrated analysis of these data indicates that arsenic compounds are concentrated onto the ash surface in the form of As(III)-S and As(V)-O species. The As(III) species have been assigned to arsenian pyrite, while As(V)-O compounds have been assigned to adsorbed arsenate ions or Fe arsenate salts precipitated as thin coatings.Although the main As carrier in the studied volcanic ashes is Al-silicate glass, this phase is stable at the neutral pH that dominates the aqueous reservoirs of the area affected by ashfall. Thus, its contribution to the pool of dissolved arsenic is minor. Higher contributions are clearly associated with the more mobile As species that concentrate onto the surface of Al-silicate glass. This more available arsenic represents less than 6% of the total measured arsenic.